Prey predator Model with Holling Type II Functional Response and Hunting Cooperation of Predators - Fitri, Davina Alma; Savitri, Dian (MATHunesa: Jurnal Ilmiah Matematika, 2024)
This research examines the interaction of two populations with Holling type II response functions and hunting cooperation in predators. The mathematical model developed is based on natural phenomena, namely the interaction between wolves and deer. Wolves often cooperate to hunt in packs, with most of their prey consisting of physically or health weak individuals, one of which is deer. The dynamics analysis begins with determining the basic assumptions of model construction, equilibrium and stability points, and numerical simulation using PPlane. The results of the dynamics analysis show that there are three equilibrium points with stability types, namely E1(0,0) , which is unstable, E2(k, 0) and E3 which is asymptotically stable under certain conditions. Numerical simulation results show the existence of double stability at equilibrium points E2 and E3 with prey to predator conversion parameter value 2.03 shows a change in stability that only occurs at point E2 . The difference in the value of prey to predator conversion affects in the change in the system solution and has an impact on reducing the predator population.